Efficient stem cell collection after modified cisplatin-based mobilization chemotherapy in patients with diffuse large b cell lymphoma - Kriegsmann, Katharina; Cremer, Martin; Schwarzbich, Mark-Alexander; Kriegsmann, Mark; Ho, Anthony Dick; Witzens-Harig, Mathias; Wuchter, Patrick (Biology of blood and marrow transplantation, 2016)
In patients with relapsed or refractory diffuse large B cell lymphoma (DLBCL), R-DHAP (rituximab, dexamethasone, cytarabine, and cisplatin) is a commonly used regimen for salvage therapy and for mobilization of peripheral blood stem cells (PBSCs). At our center, a modified R-DHAP regimen with administration of 25 mg/m2 cisplatin as a 3-hour infusion over 4 consecutive days, instead of a single infusion of 100 mg/m2 over 24 hours, has been established. The aim of this study was to analyze the efficiency of this modified R-DHAP regimen plus G-CSF as a mobilization strategy. We retrospectively analyzed clinical characteristics, PBSC collection and autologous stem cell transplantation parameters, and hematologic reconstitution data for 65 patients with relapsed or refractory DLBCL who underwent PBSC collection after mobilization with the modified R-DHAP protocol at our institution between 2002 and 2013. Data were evaluated for the overall cohort and with regard to the number of R-DHAP cycles received before PBSC collection. PBSC collection was performed after the first R-DHAP course in 32 patients (49%), after the second course in 30 patients (46%), and after the third course in 3 patients (5%). Sixty-three patients (97%) achieved the collection goal of ≥2.0 × 106 CD34+ cells/kg body weight. A significantly higher median CD34+ cell collection yield was achieved when cells were collected after the first R-DHAP course compared with after the second course (P < .01). A peripheral blood leukocyte increase of ≥1.0 × 109/L and a platelet increase of ≥20 × 109/L were observed by 11 days after ASCT. In our cohort, the modified R-DHAP regimen proved safe and feasible, showed an overall response rate (complete response, complete response unconfirmed, and partial response) of 66%, and allowed efficient mobilization of CD34+ cells for PBSC collection.
Gesehen am 28.05.2020